2000
DOI: 10.1556/aphyt.34.1999.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seed-born Colletotrichum lindemuthianum on French bean seed quality

Abstract: French bean seed samples were collected from different parts of Tamil Nadu including both tropical and temperate region including four cultivars viz., Arkakomal, Premier, Rajmash DPU 88-4 and Watex. The variety Watex was found to maximum per cent seed infection of C. lindemuthianum with more discolorations. Among the various techniques adopted for detection, agar plate method was found to be best and yielded maximum per cent seed infection. Direct correlation was obtained between seed discoloration and per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The relationships were evident between infection levels in the pods and seed infection, as determined by seedling grow-out in laboratory tests reported by Vechiato et al [32]. These results are in line with those reported by Ravi et al [33] in that agar plate incubation was found to be the best and yielded maximum percentage of seed infection. The percentage of infected seed is an important determines factor and indicates virulence of the pathogen during the growing season since the secondary inoculum produced will be proportional to the amount of initial inoculum [34].…”
Section: Effect Of Soil Solarization and Fungicide Applications On Sesupporting
confidence: 90%
“…The relationships were evident between infection levels in the pods and seed infection, as determined by seedling grow-out in laboratory tests reported by Vechiato et al [32]. These results are in line with those reported by Ravi et al [33] in that agar plate incubation was found to be the best and yielded maximum percentage of seed infection. The percentage of infected seed is an important determines factor and indicates virulence of the pathogen during the growing season since the secondary inoculum produced will be proportional to the amount of initial inoculum [34].…”
Section: Effect Of Soil Solarization and Fungicide Applications On Sesupporting
confidence: 90%
“…Neem (Azadirachta indica) seed extract effectively inhibited both germination of conidia and mycelial growth of C. lindemuthianum [52]. Seed treatment and field spray using the extracts of Lawsonia inermis significantly improved seedling emergence and reduced incidence of bean anthracnose [53].…”
Section: Biological Controlmentioning
confidence: 99%
“…The integration of soil solarization, Mancozeb seed treatment at a rate of 3 g/kg seeds and Carbendazim foliar spray at a rate of 0.5 kg/ha were found to be effective in reducing bean anthracnose epidemics [46]. Botanicals and biopesticides (10% extracts of Adenocalymma alliaceae, Azadirachta indica and Lawsonia inermis, 0.4% talc formulation of T. viride and Pseudomonas fluorescens along with fungicides (Carbendazim (0.2%) and Mancozeb (0.4%) were evaluated in a greenhouse and field experiment in India and gave promising results [53].…”
Section: Integrated Disease Managementmentioning
confidence: 99%
“…Pod infection usually leads to seed infection and discoloration (Schwartz et al, 2005). Seed infection has been shown to reduce germination and seedling vigour (Ravi et al, 1999). The use of pathogen-free seed is one of the key components in an integrated strategy for the control of this disease (Schwartz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%